Overview of COVID-19 Vaccination Status in Patients Infected with COVID-19 at the Royal Prima General Hospital Medan - Lavenia Tri Setiani; Wienaldi; Wika Hanida Lubis (HM Publisher, 2023)
Since the start of the COVID-19 pandemic, attempts have been made to provide acquired immunity against COVID-19. Monitoring and evaluating the efficacy and safety of the COVID-19 vaccine is an important process that must always be carried out in order to optimize the control of the spread of COVID-19 infection. This study aimed to provide an overview of the status of COVID-19 vaccination in patients infected with COVID-19 at the Royal Prima General Hospital, Medan, Indonesia. This study was a descriptive observational study. A total of 100 subjects participated in this study. Data analysis was performed using SPSS version 25 in a univariate manner. The majority of patients who have been vaccinated against COVID-19 only experience mild symptoms of COVID-19. The majority of vaccine brands used by confirmed COVID-19 patients are Sinovac. The majority of patients who have received 2 doses of vaccination are still at risk of being infected with COVID-19. The majority of patients who received the COVID-19 vaccination experienced a low clinical degree when infected with COVID-19.